(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we employ the method of increment operators, by means of the left invariant operators &#163^v,s on nilpotent Lie group G^d_1+d_2 and the calculus of v- &PsiDOs, to discuss the hypoellipticity for a class of nonprincipal type LPDOs &#163 on a d_1 + d_2 dimensional manifold M. For those hypoelliptic &#163 we also construct their parametrices.